Hemorrhoidectomy: Open or closed technique? A prospective, randomized clinical trial - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2002)
PURPOSE: Hemorrhoidectomy is the treatment of choice for patients with third-degree or fourth-degree hemorrhoids. However, whether the closed or open technique yields better results is unknown. The purpose of this study was to compare these techniques with respect to operating time, analgesic requirement, hospital stay, morbidity rate, duration of inability to work, healing time, and follow-up results. METHODS: In this prospective and randomized study, 80 patients with third-degree or fourth-degree hemorrhoidal disease were allocated to either the open-hemorrhoidectomy (Group A, n = 40) or the closed-procedure group (Group B, n = 40). Open hemorrhoidectomy was performed according to the St. Mark's Hospital technique, whereas the Ferguson technique was used for the closed procedure under general anesthesia with the patient in the jackknife position. RESULTS: Mean operating time was significantly shorter in Group A (35 7 vs. 45 8 minutes, P < 0.001). Analgesic requirement on the day of surgery and the first postoperative day was also significantly lower (P < 0.05). The morbidity rate was higher in Group B (P < 0.05). Length of hospital stay and duration of inability to work were similar in both groups (P > 0.05). Healing time was significantly shorter in Group B (2.8 +/- 0.6 vs. 3.5 +/- 0.5 weeks, P < 0.001). Median follow-up time was 19.5 (range, 4-40) months. The only late complication (anal stenosis) was observed in one patient in Group B. CONCLUSIONS: Although the healing time is longer, the open technique is more advantageous with respect to shorter operating time, less discomfort in the early postoperative period, and lower morbidity rate.
Keywords: URINARY RETENTION; OPERATIONS